2018
DOI: 10.1093/femspd/fty001
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of antimicrobial peptides in corneal infection and regulation of antimicrobial peptides and reactive oxygen species by type III secretion system of Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen and is the major cause of corneal infection worldwide that secret several virulent toxins through its type III secretion system (T3SS). In defense against pathogenic insults, epithelial cells and macrophages express antimicrobial peptides (AMPs) that are essential components of host immune response. In this study, we have determined the expression of several AMPs in patients with P. aeruginosa corneal infection. We also used an in vitro model of infection usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 54 publications
2
27
0
Order By: Relevance
“…Genes among the Clinical Isolates of P. aeruginosa P. aeruginosa has a repertoire of toxins secreted by different secretory pathways. T3SS is one of the major virulence factors that have been shown to subvert host immune responses, including reactive oxygen species generation, in human corneal epithelial cells [42,43]. In this study, we screened thirty four ocular clinical isolates causing corneal infections and determined the presence of genes associated with virulence such as the main T3SS effector genes, exoS, exoT, exoU and exoY, as well as pscU and pscT, responsible for T3SS machinery [44].…”
Section: Differential Expression Of T3ssmentioning
confidence: 99%
“…Genes among the Clinical Isolates of P. aeruginosa P. aeruginosa has a repertoire of toxins secreted by different secretory pathways. T3SS is one of the major virulence factors that have been shown to subvert host immune responses, including reactive oxygen species generation, in human corneal epithelial cells [42,43]. In this study, we screened thirty four ocular clinical isolates causing corneal infections and determined the presence of genes associated with virulence such as the main T3SS effector genes, exoS, exoT, exoU and exoY, as well as pscU and pscT, responsible for T3SS machinery [44].…”
Section: Differential Expression Of T3ssmentioning
confidence: 99%
“…In our earlier study we investigated the expression of AMPs from corneal scrapings of patients with P. aeruginosa corneal infections and saw differential expression of several AMPs, including human β defensins (hBD) 2, and 3, S100A9, S100A12 and LL-37. We also found that PAO1 subverts the expression of these AMPs in HCECs in vitro [ 6 ]. However, we observed that the expression of the AMPs increased significantly when cells were exposed to PAO1Δ pscC , a T3SS mutant that fails to transfer exotoxins to the host cells.…”
Section: Resultsmentioning
confidence: 99%
“…In the cornea, P. aeruginosa activates the Toll like receptors (TLRs) that results in prompt production of cytokines and chemokines, recruitment of immune cells to the cornea and development of corneal opacity [ 2 ]. The corneal epithelium provides the first line of defense against invading bacteria [ 3 ] and the host immune response to P. aeruginosa is regulated by TLR4-MD-2 and TLR5 leading to an elevated expression of proinflammatory cytokines and antimicrobial peptides (AMPs) [ 2 , 4 6 ]. One of the fundamental virulence factors of P. aeruginosa is the type III secretion system (T3SS) which consists of a syringe-like apparatus that functions in a highly controlled manner to transport bacterial toxins and other proteins into the host cells [ 7 ] and amend different functions of the host to survive [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a T3SS in P. aeruginosa, shared with many other Gram-negative bacteria, which transfer effector toxins directly from the bacterium into the host cell cytosol [11]. P. aeruginosa can repress AMP expression in both epithelial cells and macrophages by its T3SS in vitro [12]. ExsA is an essential transcriptional activator of T3SS in P. aeruginosa.…”
mentioning
confidence: 99%